For Love, Money and Status, or Personal Growth? A Survey of Young Emirati Women’s Educational Aspirations - Woohyang Sim (Gulf Education and Social Policy Review)
Abstract The United Arab Emirates has been in the spotlight in recent years in light of its rapid growth and development. A key area of interest is the expansion of education, especially higher education for women, which has witnessed enormous growth in the last decade. However, despite the rapid increase in female higher education enrollment, women's labor participation remains low, leading to questions on why highly educated young women are not in employment. This study investigates the incongruence between the growth of female attainment of higher education and women's career inactivity over the last decades. To explore this mismatch, the study examines Emirati women's perception of the role of higher education, analyzed through examining their educational and career aspirations and the correlations between these two. The study finds that for Emirati women, education is not always a means to an end, but simply the end itself. For some women, education is related to supplementing personal growth and contentment. The findings suggest that Emirati women aspire to further their education, especially through earning doctorate degrees. However, they do not necessarily connect their education to their intended future occupation. The findings provide an alternative explanation of the disconnect between women's educational outcomes and labor market participation and provide insight into Emirati women's choice to remain unemployed.